The effects of Ba2+ content on depolarization temperature and pyroelectric properties of lead-free 0.94Na0.5Bi0.5TiO3-0.06Ba1+xTiO3 ceramics - Balakt, Ahmed M.; Shaw, Christopher P.; Zhang, Qi (Springer, 2016)
Lead-free 0.94Na0.5Bi0.5TiO3–0.06Ba1+xTiO3 (NBT–0.06B1+xT) ceramics (0.0 ≤ x ≤ 0.03) were synthesized by a conventional solid-state reaction process. X-ray diffraction shows that the compositions are at the morphotropic phase boundary where rhombohedral and tetragonal phase coexist. Grain size slightly changes with the increase of Ba2+ content and reaches the minimum at x = 0.02. The depolarization temperature (Td) decreases with the extra Ba2+content but the lowest Td was obtained at x = 0.01–0.02. The pyroelectric coefficient (p) was measured as a function of Ba2+ content, and increased from 2.90 × 10−4 to 3.54 × 10−4 C m−2 °C−1, and from 55.3 × 10−4 to 740.7 × 10−4 C m−2 °C−1 for x = 0.00 and 0.02 at RT, and depolarization temperature (Td) respectively. The pyroelectric coefficient (p) shows a large increase with rising the temperature and reaches the maximum value at the depolarization temperature (Td). The figures of merits of Fi, Fv and FD have all been improved with the addition of extra barium. These improved pyroelectric properties indicate that NBT–0.06B1+xT is a promising material for pyroelectric applications or a wide range of temperature.